PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI DHARMA NILA FARM KALURAHAN SENDANGTIRTO KEMANTREN BERBAH KAPANEWON SLEMAN - Sutendi, Faktori; Yunianta, Yunianta; Ratri, Wahyu Setya (Fakultas Pertanian UST, 2024)
This study aims to analyze the influence of motivation and work discipline on employee productivity at Dharma Nila Farm Sendangtirto Kemantren Berbah Kapanewon Sleman. The basic method used in this research is quantitative descriptive method. The population in this study were 33 employees at Dharma Nila Farm, using saturated samples, namely all employees of Dharma Nila Farm. The data analysis method in this study is to use multiple linear regression analysis, to determine the effect of the independent variable (X) on the dependent variable (Y). The results of the analysis show the Adjusted R Square determination value of 0.677, meaning that the Motivation (X1) and Work Discipline (X2) variables affect Work Productivity (Y) 67.70% while the remaining 32.30% is influenced by variables such as age and other jobs. The regression equation Y = 3.290 + 0.733 X1 + 0.471 X2 + e. Based on the results of the F test that the significance value for the effect of motivation and work discipline variablessimultaneously on work productivity is 0.000 Ftable 3.30, then the alternative hypothesis is accepted. Based on the results of the t test, the motivation variable obtained a sig value of 0.003 and a sig value of work discipline of 0.000, meaning that the significant value is smaller than the probability value <0.05, then motivation and work discipline have a significant effect partially on employee produktivicy. This shows motivation and work discipline are good measures of employee performance that will increase employee productivity at Dharma Nila Farm. It is recommended that efforts be made to improve motivation and work discipline.